Atropine augments cardiac contractility by inhibiting cAMP-specific phosphodiesterase type 4 - Perera, Ruwan K.; Vettel, Christiane (Scientific reports, 2017)
Atropine is a clinically relevant anticholinergic drug, which blocks inhibitory effects of the parasympathetic neurotransmitter acetylcholine on heart rate leading to tachycardia. However, many cardiac effects of atropine cannot be adequately explained solely by its antagonism at muscarinic receptors. In isolated mouse ventricular cardiomyocytes expressing a Förster resonance energy transfer (FRET)-based cAMP biosensor, we confirmed that atropine inhibited acetylcholine-induced decreases in cAMP. Unexpectedly, even in the absence of acetylcholine, after G-protein inactivation with pertussis toxin or in myocytes from M2- or M1/3-muscarinic receptor knockout mice, atropine increased cAMP levels that were pre-elevated with the β-adrenergic agonist isoproterenol. Using the FRET approach and in vitro phosphodiesterase (PDE) activity assays, we show that atropine acts as an allosteric PDE type 4 (PDE4) inhibitor. In human atrial myocardium and in both intact wildtype and M2 or M1/3-receptor knockout mouse Langendorff hearts, atropine led to increased contractility and heart rates, respectively. In vivo, the atropine-dependent prolongation of heart rate increase was blunted in PDE4D but not in wildtype or PDE4B knockout mice. We propose that inhibition of PDE4 by atropine accounts, at least in part, for the induction of tachycardia and the arrhythmogenic potency of this drug.